INTRODUCTION TO ROUTING PROTOCOLS (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In this era of communication network, we can access any website or contact any person with the help of internet or telephone anywhere in the world without knowing where the website is hosted and without knowing where the person is located. This all is done within a few seconds very efficiently. But the question comes out how it is done? And the answer is that, it is only done with the help of network routing. In this paper we review the IP routing and its protocols.